Mosby's 2012 nursing drug reference - Roth, Linda Skidmore (St. Louis, Missouri : Elsevier Mosby, 2012)
Contains alphabetically arranged entries that profile over 1,300 generic and 4,500 trade medications, describing the uses, side effects, interactions, classifications, controlled-substance schedules, nursing considerations, and other aspects of each.
Drug categories -- Color insert -- Individual drugs -- Appendixes -- Index.
Includes index.
Keywords: DRUGS HANDBOOKS, MANUALS, ETC; NURSING HANDBOOKS, MANUALS, ETC